The Dynamics of Policies for Implementing Religious Moderation and Local Wisdom in the State Islamic Institute Kudus, Indonesia - Muhammad Miftah; Abu Choir; Fikri Ihsan Khairuddin (Universitas Muhammadiyah Malang, 2023)
This research analyzes the role of Islamic religious universities in maintaining local wisdom through integrating local wisdom with religious moderation. The existence of a state Islamic religious college in the community is the basis for the resilience of local wisdom in the environment where the college is located. The locus of this research is located at IAIN Kudus, Central Java. This research uses a descriptive-qualitative approach to uncovering phenomena and facts in the field. It is hoped that the results of this research will provide a comprehensive picture of the implementation of religious moderation policies and local wisdom in Islamic institutions. Data analysis in this research seeks to identify challenges, opportunities, and the impact of this policy on inter-religious harmony, religious learning, and student character development. In addition, this research also evaluates the extent to which this policy reflects the principles of tolerance, diversity, and local wisdom in the context of Islamic higher education. Through an in-depth understanding of the dynamics of policies for implementing religious moderation and local wisdom at IAIN Kudus, it is hoped that this research can contribute to improving policies and more effective implementation at the institutional level, as well as providing a broader view regarding the harmonization of diversity in the context of Islamic education in Indonesia. The results of this research can be explained by the fact that the integration of local wisdom and religious moderation in the tertiary environment has proven to be able to realize the understanding and application of the importance of religious moderation values in tertiary institutions.